2015
DOI: 10.1016/j.cyto.2015.07.027
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 inhibits apoptosis of exocrine gland tissues under inflammatory conditions

Abstract: Interleukin (IL)-6 is a multi-functional cytokine that can either promote or suppress tissue inflammation depending on the specific disease context. IL-6 is elevated in the exocrine glands and serum of patients with Sjögren’s syndrome (SS), but the specific role of IL-6 in the pathogenesis of this disease has not been defined. In this study, we showed that IL-6 expression levels were increased with age in C56BL/6.NOD-Aec1Aec2 mice, a primary SS model, and higher than the control C57BL/6 mice. To assess the rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 60 publications
1
12
0
1
Order By: Relevance
“…In order to further characterise the SG microenvironment in relation to adipose tissue replacement, we examined the expression pattern of IL-6; a proinflammatory cytokine [45] with antiapoptotic and tissue protective functions [46][47][48]. Through immunohistochemical staining of SG biopsies, IL-6 was detected in FI rich regions in both SS patients and non-SS controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to further characterise the SG microenvironment in relation to adipose tissue replacement, we examined the expression pattern of IL-6; a proinflammatory cytokine [45] with antiapoptotic and tissue protective functions [46][47][48]. Through immunohistochemical staining of SG biopsies, IL-6 was detected in FI rich regions in both SS patients and non-SS controls.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesise that there could be a predictive relationship between the stage of disease and adipose tissue replacement in the gland. Furthermore, it has previously been shown that adipocytes express interleukin-6 (IL-6), which is a proinflammatory cytokine [45], yet with both antiapoptotic and tissue protective functions [46][47][48]. This is why we wished to examine the expression of IL-6 in relation to fatty replacement in the SG tissue of SS patients, and further explore the SG microenvironment.…”
Section: Introductionmentioning
confidence: 96%
“…ESCs were cultured in DMEM supplemented with 10% FBS. When the cells reached approximately 80% confluence, the medium was removed and replaced with serum-free medium, with addition of 10 −8 mol/l estrogen (E 2 ), 10 −7 mol/l progestin (P), 10 −8 mol/l E 2 + 10 ng/ml recombinant IL-6 [ 18 ], 10 −7 mol/l P + 10 ng/ml IL-6, 10 −8 mol/l E 2 + 10 −7 mol/l P, or 10 −8 mol/l E 2 + 10 −7 mol/l P + 10 ng/ml IL-6 (PeproTech, Oak Park, CA, USA). The cells were cultured for 24 h, and the supernatant was collected as conditioned medium.…”
Section: Methodsmentioning
confidence: 99%
“…On the other side, it has been reported that suppression of autophagy by PI3K/AKT activation accelerates tumor growth due to inflammation [34,35]. Interleukin-6, a family of cytokinesis, is usually associated with inflammation during carcinogenesis and has been reported to inhibit or delay apoptosis [36][37][38]. IL-6 is considered as a malevolent player that promotes tumor initiation and macrophages infiltration and is found to be closely related to STAT3 (Signal Transducers and Activators of Transcription-3) [38][39][40].…”
Section: Introductionmentioning
confidence: 99%